Factors affecting the performance of dynamic source routing protocol in mobile ad hoc networks using taguchi approach [electronic resource] - 260625 Mazalan Sarahintu; Abd. Aziz Jemain; Robiah Adnan, supervisor; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2008